Business security consulting service as an object of accounting - O.Yu. Shyrokopoias (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
This article focuses on business security consulting services as an object of accounting. The analysis of the scientific literature has shown that the issues of management and accounting of consulting services in the field of business security are currently poorly understood in domestic economic science. The study showed that the chosen object of study borders on the edge of economics, law and public administration. Analysis of consulting services as an object of accounting, which will allow to develop and substantiate innovative approaches to the formation of information and analytical support of management of consulting companies, and for the customer will allow to create information support for evaluating the effectiveness of such service in terms of business security. The article deals with the properties of consulting services, depending on the types of services, in particular: in the field of financial and economic security, in the field of cybersecurity, in the field of security and law enforcement, and the accounting objects for each type. The specifics of the consulting service as an object of accounting were revealed, but in the context of its substantive content, it should be noted that the fundamental specificity of the consulting service in the field of business security is that the time interval of the production and sales process coincides, that is, the process of providing consulting services in the sphere business is also a process of its realization. In addition, if security consulting services provide for certain types of work and sales of goods, these processes may also coincide in time. This significantly complicates the accounting system in terms of identifying revenues in the implementation of goods, works, services and in terms of distribution of overhead costs and costing consulting services in the field of security.